Noise Figure Characteristics of Erbium Doped Fiber Amplifiers at single and multiple amplified stage - Ragheed M. Ibrahim; Nawzat S. Saadi; Saad F. Ramadhan (College of Education for Pure Sciences, 2012)
Abstract In this study, an Erbium Doped Fiber Amplifier (EDFAs) simulation program has been written in Matlab to characterize Noise Figure variations of a forward pumped EDFAs operating in C band (1525-1565 nm) as functions of Er3+ fiber length, injected pump power, signal input power and Er3+ doping density. The effect of multiple amplified stage on the noise figure was student at different Fiber length and pumping power. The numerical results shows that EDFAs could be operated in saturation regimes leading minimum noise figure when the EDFAs is supplied with sufficient pump power, Moreover a continuous increasing of the noise figure value was demonstrated by increasing all of amplified stage number and fiber length.